2012
DOI: 10.1089/pop.2011.0068
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Obesity Management Among Physicians

Abstract: Despite the strong recommendations of guidelines, intensive obesity management is not offered to all obese patients. This study aimed to examine differences in obesity management between primary care physicians (PCPs) and non-PCPs. A cross-sectional study was performed using the 2006-2007 National Ambulatory Medical Care Survey. Adults (age ≥20 years) with obesity (body mass index (BMI)≥30 kg/m(2) or obesity diagnosis using International Classification of Diseases, Ninth Revision, Clinical Modification code 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Similar results have been previously reported in the adult population. Mehta et al 8 reported that less than one-third of preventive ambulatory visits in an obese adult population resulted in obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been previously reported in the adult population. Mehta et al 8 reported that less than one-third of preventive ambulatory visits in an obese adult population resulted in obesity management.…”
Section: Discussionmentioning
confidence: 99%
“…PCPs recognize the priorities and issues that accompany treating obese and overweight individuals, such as sufficient time for educating and counseling patients. PCPs need a minimum of 20–30 minutes to spend with obese patients especially those with multiple co-morbidities 41 instead of the usual 10–15 minutes for an office visit. In other words, practice guidelines suggest specific interventions for this population require more time - even for follow up visits 42 .…”
Section: Pcps Influence On Obesity Healthcare Policymentioning
confidence: 99%